Perception Analysis of Installation Services Quality on Patient Satisfaction at Bhayangkara Hospital Level II Medan - Gisna hartini; Arifah Devi Fitriani; Iman Muhammad (Journal La Medihealtico, 2021)
The purpose of this research is to analyze the influence of patient perception about professionalism, efficiency, patient safety and access of service to patient satisfaction at Inpatient Bhayangkara TK II Hospital Medan. The type of research used in this study is an analytical survey (explanatory research) with Cross-Sectional Study study design. The number of samples in this study were 54 patients who got service at the inpatient installation. Sampling technique by Accidental Sampling. The result of this research shows that the result of bivariate analysis to select multivariate analysis modeling candidate is statistically tested by using chi square test found that from the four variables all entered as multivariate modeling candidate. Then from the result of multivariate statistic test, it was found that p value (Sig) of professional variable (p = 0,024), efficiency (p = 0,025), access (p = 0,022) and patient safety (p = 0,048) which is significant to patient satisfaction at Inpatient Installation of Bhayangkara TK II Hospital Medan. The conclusion of the research shows that there is influence of service quality of inpatient installation which consist of profession, efficiency, access to service and patient safety to patient satisfaction. It is hoped that this research can make an actual input for health workers and the hospital. It is recommended that health workers carry out their duties according to the work SOP. Improve internal communication so that cooperation between health partners can run well in improving service quality and patient satisfaction.